ROLE OF ULTRASOUND IN ACUTE APPENDICITIS - Mardan, Mohammad Akbar Ali; Mufti, Tariq Saeed; Khattak, Irfan Uddin; Chilkunda, Nagendra; Alshayeb, Abdulmonem A.; Mohammad, Ahmad Moussa; Rehman, Zia ur (Journal of Ayub Medical College Abbottabad, 2007)
Background: Misdiagnosis of acute appendicitis is a common and crucial problem in general surgery. Graded compression ultrasonography is one of the new diagnostic technique that is reported to have improve the diagnostic accuracy and clinical outcome. The aim of current study is to assess the role of this diagnostic modality in the management of acute appendicitis. Methods: This is a cohort observational study comparing the adverse outcome in two different groups of patients admitted with suspected acute appendicitis at two different hospitals in two different countries. The first group of 200 patients at Ayub Teaching Hospital Abbottabad, Pakistan, was managed without preoperative ultrasonography. In the second group of 200 patients admitted at Najran General Hospital Najran Saudi Arabia, graded compression abdominal ultrasonography was routinely performed preoperatively. Diagnostic accuracy of the protocol in each group was measured statistically and rates of negative appendicectomy and perforation were determined. Results: Addition of routine ultrasonography in clinical assessment for acute appendicitis decreases the sensitivity but significantly increases the specificity of the protocol thereby reducing the false positive rate translating into decreased negative appendicectomy rate. Rate of negative appendicectomy was 22.5% in group one and 4.7% in group two.Perforation rate was 15.6% in group 1 and 15% in group two. Conclusion: Proper clinical assessment is the mainstay of diagnosis in acute appendicitis and addition of routine ultrasound by graded compression technique can improve the diagnostic accuracy and adverse outcome. Key Words : Acute Appendicitis, Ultrasonography, Diagnosis,